Current biomarkers of prostate cancer - I. A. Aboian; E. N. Fedotova; A. N. Shevchenko; S. M. Pakus; A. Yu. Maximov; E. V. Filatova; I. A. Khomutenko; Е. F. Komarova; N. K. Guskova (Исследования и практика в медицине)
Prostate cancer is one of the most common malignancies in men. Early detection of prostate cancer is largely determined by the widely used prostate specific antigen (PSA) blood test. However, as a diagnostic and prognostic test of prostate cancer, PSA has limited specificity, sensitivity and leads to hyper or underdiagnosis, which, in turn, can lead to excessive treatment. There fore, it is very important to develop diagnostic markers that can be used to determine prostate cancer at an early stage of development, assess the possible progression of the disease and prescribe optimal therapy. Significant progress has been made in the discovery of biomarkers for prostate cancer. For example, biomarkers such as %-free PSA, Prostate Health Index (PHI) or 4K score can be used to increase specificity and reduce the number of unnecessary biopsies, while the PCA3 test can be used to reduce the number of repeated biopsies in men with previously negative biopsy. To determine aggressiveness and predict the outcome of the disease, tissue multigenic tests can be used, such as: T2-ERG, ExoDx, SelectMDx and ConfirmMDx, Prolaris, Oncoytype DX, Decipher. The development of such diagnostic tests opens up new opportunities for improving the diagnosis of prostate cancer, prognosis and decision-making on the appointment of therapy. And with the increase in their availability, finally, the possibility of an individual approach to the appointment of treatment for men with prostate cancer appears on the horizon. This review paper presents the data on the most advanced diagnostic biomarkers of prostate cancer.